2016
DOI: 10.1016/j.addbeh.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of co-ingestion of prescription tranquilizers and other psychoactive substances by U.S. high school seniors: Results from a national survey

Abstract: Introduction Nonmedical tranquilizer use (NMTU) is a concerning and understudied phenomenon in adolescents, despite being the second most prevalent form of nonmedical use in this population. Thus, this work aimed to examine the sociodemographic and substance use correlates of past-year co-ingestion of a prescription tranquilizer and another substance among adolescents. Methods Data were from the Monitoring the Future study, a nationally representative survey of US high school students. Data from 11,444 senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 18 publications
4
30
2
9
Order By: Relevance
“…This study found that more than nine in every ten adolescents who reported NMPSA engaged in polysubstance use during the past-year which is similar to prior studies examining nonmedical use of prescription opioids, sedatives, stimulants and anxiolytics (McCabe et al, 2006; Catalano et al, 2011; Schepis et al, 2016). In fact, recent work has shown that the majority of past-year nonmedical users of prescription opioids, anxiolytics and sedatives engage in simultaneous co-ingestion with at least one other substance placing such individuals at increased risk of consequences such as overdose (McCabe et al, 2006; McCabe and Boyd, 2005; SAMHSA, 2012, 2013; Schepis et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study found that more than nine in every ten adolescents who reported NMPSA engaged in polysubstance use during the past-year which is similar to prior studies examining nonmedical use of prescription opioids, sedatives, stimulants and anxiolytics (McCabe et al, 2006; Catalano et al, 2011; Schepis et al, 2016). In fact, recent work has shown that the majority of past-year nonmedical users of prescription opioids, anxiolytics and sedatives engage in simultaneous co-ingestion with at least one other substance placing such individuals at increased risk of consequences such as overdose (McCabe et al, 2006; McCabe and Boyd, 2005; SAMHSA, 2012, 2013; Schepis et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…The majority of adolescents who report NMPSA engage in concurrent or simultaneous polysubstance use (McCabe et al, 2006, 2007; Schepis et al, 2016), creating major challenges to isolating drug-specific-related problems resulting from NMPSA. For instance, nearly 73% of adolescent past-year nonmedical users of prescription anxiolytics simultaneously co-ingested these medications with at least one other substance, primarily cannabis and alcohol (Schepis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying simultaneous substance use is important because such use represents the experiences of many young substance users (Schepis et al, 2016; Subbaraman and Kerr, 2015). We identified situational and social characteristics associated with simultaneous use of alcohol and marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…Although simultaneous use (i.e., use of more than one substance within a few hours) is common among young substance users (Pape et al, 2009; Schepis et al, 2016; Subbaraman and Kerr, 2015), we know very little about contexts and risks associated with simultaneous use of alcohol and marijuana. We know that risks for underage drinking vary from one context to another and that drinking contexts, independently of how much a person drinks, are related to specific problems (Bersamin et al, 2016; Lipperman-Kreda et al, 2015; Mair et al, 2015), but we do not know if contexts of simultaneous alcohol and marijuana use are unique or whether simultaneous use leads to greater problems.…”
Section: Introductionmentioning
confidence: 99%